Microstrip patch antenna array at 5.8 GHz for point to point communication - A. Rahim, Mohamad Kamal; Asrokin, A.; Jamaluddin, Mohd. Haizal; Ahmad, Mohd. Ridzuan; Masri, Thelaha; Abd. Aziz, Mohamad Zoinol Abidin (2006)
This paper described the design of microstrip patch array antenna with operating frequency at 5.8GHz for point to point communication. The array of four microstrip rectangular patch antennas with inset feed based on quarter-wave impedance matching technique were designed, simulated, fabricated and measured with the aid of microwave office software. The simulation and measurement result met the IEEE 802.11a standard and able to operate in upper UNII band for point to point communication. The 4times4 array has a return loss of -30.42 dB with 15% bandwidth. The gain obtained from simulation is 16 dB with 9deg half power beamwidth (HPBW).